A Matter of Location: The Role of Regional Social Capital in Overcoming the Liability of Newness in R&D Acquisition Activities. Issue 9 (1st September 2016) - Laursen, Keld; Masciarelli, Francesca; Reichstein, Toke
Abstract : Laursen K., Masciarelli F. and Reichstein T. A matter of location: the role of regional social capital in overcoming the liability of newness in R&D acquisition activities, Regional Studies . External knowledge acquisition is a precondition for firms' competitive advantage. However, young firms exhibit a lower propensity to acquire external research and development (R&D) than their older counterparts. The paper explores the role of regional social capital in moderating this aspect of the liability of newness. The results show that young firms operating in regions with low levels of social capital are less likely to acquire R&D externally. However, this is not the case in regions with high levels of social capital, suggesting that the liability of newness in terms of acquisition of external R&D does not play a role in these regions.